If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6a + 8) = 4 + 6a Reorder the terms: 2(8 + 6a) = 4 + 6a (8 * 2 + 6a * 2) = 4 + 6a (16 + 12a) = 4 + 6a Solving 16 + 12a = 4 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. 16 + 12a + -6a = 4 + 6a + -6a Combine like terms: 12a + -6a = 6a 16 + 6a = 4 + 6a + -6a Combine like terms: 6a + -6a = 0 16 + 6a = 4 + 0 16 + 6a = 4 Add '-16' to each side of the equation. 16 + -16 + 6a = 4 + -16 Combine like terms: 16 + -16 = 0 0 + 6a = 4 + -16 6a = 4 + -16 Combine like terms: 4 + -16 = -12 6a = -12 Divide each side by '6'. a = -2 Simplifying a = -2
| 3(x+5)/2=-18 | | 2a+5=6a+9 | | a+3b-c=20 | | 5=-x-5 | | 7(3n-1)=(2n+4)+2 | | 2x-2xc= | | 3(2x-6)=6(x-6) | | 5=2a | | X^2+10=131 | | 6a-(a-1)=4 | | 6x-91=3x-10 | | 214-2x=34x+18 | | 9-6z=27 | | 4g+3(-7+2g)=1-g | | 14-7x=174-42x | | 2g+4(-6+2g)=1-g | | 36x=x*(r*r) | | 6x-91=3x-2 | | t^2-2t-36=0 | | -6g-4=-3g+2 | | 3x-4=4x-2 | | 3x-4=4x-ray | | -8=-2a+6 | | x^3-7x= | | 3x+29=11x-43 | | -6m+69-9(m-1)=4m-(2m-2)-7m+6 | | 10y^2-19y+6=0 | | 6p-8=8-30p | | 93=9*(e^2x) | | 2x+8=64-4x | | -3r+7=5r-3 | | 5.2y+7.2=30.6-1.3y |